The Leadership of Schools in Improving The Quality of Education in The 18 State Basic Schools of Air Kumbang - Jayanti, Evi Sri; Harapan, Edi; Wardiah, Dessy (Jurnal Pendidikan Tambusai, 2021)
This study aims to determine and describe the objectives to be achieved with this research is to identify and describe the leadership of the principal in improving the quality of education in 18 Air Kumbang public elementary schools. The method used is a qualitative method. Data collection techniques using observation, interviews and documentation. The results of this study indicate that the role of leadership is the behavior or activity that a person displays through the attitudes and values expected in his leadership. The leadership role played by the principal of the 18 Air Kumbang public elementary school as an educator, manager, administrator, supervisor, leader, innovator, and motivator has an effect on efforts to improve the quality of education at SD Negeri 18 Air Kumbang. This has implications so that in the future the leadership role played by the principal as an educator, manager, administrator, supervisor, leader, innovator, and motivator can be carried out so that the quality of education in schools can be in accordance with the expected goals.